Mauritius : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Payment Systems, Monetary and Financial Policy Transparency, and Anti-Money Laundering. (IMF Staff Country Reports; Country Report ;, 2003)
The Financial System Stability Assessment of Mauritius assesses the standards and codes and the potential risks and vulnerabilities of the financial system. It summarizes the assessments of the standards and codes on the Basel Core Principles for effective banking supervision, systemically important payment systems, the IMF code of good practices on transparency in monetary and financial policies, and the antimoney laundering and combating the financing of terrorism. It provides input in formulating the overall assessment of financial stability, and an action plan in areas of nonobservance.